Analisis komposisi zat gizi dan antioksidan beberapa varietas labu kuning (Cucurbita moschata Durch) - Nur Rahman; Rahayu Astuti (AGROINTEK, 2022)
Pumpkin fruit consists of three parts, namely the outer skin is very strong and hard, yellow, green, cream or light brown. The thick middle part is fleshy, yellow, and can be eaten by fruit and the inner or middle part contains fiber and seeds. This study aims to compare the nutrients and antioxidants in several varieties of pumpkin. Pumpkins were obtained from the Ampel Boyolali area, Central Java, peeled the skin and separated from the flesh. The skin, flesh and inner part were considered to measure the proportion, while the flesh was analyzed for proximate, fiber content, vitamin C content, phenol content, ß-carotene content and antioxidant activity. Various varieties of pumpkin studied had significant differences in proximate, fiber, vitamin C, total phenol, ß-carotene and antioxidant activity. The Bokor pumpkin type has a higher amount of solids, protein and carbohydrates than other types. Kabocha pumpkin has a higher amount of fiber, vitamin C, fat, phenol and ß-carotene and antioxidant activity than other types